2019
DOI: 10.1371/journal.pone.0220696
|View full text |Cite
|
Sign up to set email alerts
|

Racial, ethnic, and income disparities in air pollution: A study of excess emissions in Texas

Abstract: Objective Excess emissions are pollutant releases that occur during periods of startups, shutdowns or malfunctions and are considered violations of the U.S. Clean Air Act. They are an important, but understudied and under-regulated, category of pollution releases given their frequency and magnitude. In this paper, we examine the demographic correlates of excess emissions, using data from industrial sources in Texas. Methods We conduct two complementary sets of analyses: one at the census tract level and one at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 47 publications
2
20
0
Order By: Relevance
“…Our results are similar to Benjamin (2011) that diverse groups improve air quality in low-income African American and Latino communities and contradicting the findings of Li et al (2019) that shows higher diverse communities positively causing excess air pollution in the USA. However, Das and DiRienzo (2010) argued that moderate level of diversity experiences the greatest environmental performance as they reap the benefits of a civically engaged society with creative, innovative and efficient human talent pool and do not bear the negative effects of a highly fractionalized society that typically suffers from poor communication and social cohesion, among other societal ills.…”
Section: Empirical Findingssupporting
confidence: 78%
“…Our results are similar to Benjamin (2011) that diverse groups improve air quality in low-income African American and Latino communities and contradicting the findings of Li et al (2019) that shows higher diverse communities positively causing excess air pollution in the USA. However, Das and DiRienzo (2010) argued that moderate level of diversity experiences the greatest environmental performance as they reap the benefits of a civically engaged society with creative, innovative and efficient human talent pool and do not bear the negative effects of a highly fractionalized society that typically suffers from poor communication and social cohesion, among other societal ills.…”
Section: Empirical Findingssupporting
confidence: 78%
“…Previous studies suggest that socioeconomic status-which is correlated to occupation and geographic locale-plays a significant role in the risk of exposure to environmental contaminants [40]. In the United States, low-income residents, which are disproportionally minorities, have a more pronounced exposure to particulate matter-emitting facilities [41,42]. Furthermore, it has been reported that Black and Hispanic women living in Chicago were more likely to reside in areas with higher ambient concentrations of heavy metals including cadmium, mercury, and lead compared to white women [43].…”
Section: Socioeconomic Status Occupation and Geographic Localementioning
confidence: 99%
“…While the authors do not directly study the health effects of excess emissions, they do provide preliminary damage estimates from an integrated assessment model (Heo 2015, Heo, Adams andGao 2016). Li, Konisky and Zirogiannis (2019) study the racial, ethnic and income disparities of excess emissions in Texas at the facility and census track level. They find that median income and percentage of Black population are positively associated with the incidence of excess emissions.…”
Section: Regulatory Backgroundmentioning
confidence: 99%